Humoral Immune Response in Acquired Immunity to Chlamydial Genital Infection of Female Guinea Pigs - Rank, Roger G. (1983)
Immunity to reinfection in the genital tract of female guinea pigs with the agent of guinea pig inclusion conjunctivitis was found to be dependent upon an intact humoral immune response. Cell-mediated immunity in the absence of humoral immunity had no apparent role in resistance to challenge infection.